Recovery of soluble proteins from Chlorella vulgaris by bead-milling and microfiltration: Impact of the concentration and the physicochemical conditions during the cell disruption on the whole process. (September 2021) - Liu, Shuli; Gifuni, Imma; Mear, Hugo; Frappart, Matthieu; Couallier, Estelle
Graphical abstract: Highlights: Three biomass concentrations were tested for bead-milling: 90, 60 and 30 g/L. The maximum amount of proteins was released after 4 min of bead-milling. A maceration of diluted ground biomass allowed better soluble proteins recovery. The best scenario limiting energy consumption led to 12 % proteins recovery. Pigments were separated from soluble proteins by membrane filtration PES0.1 μm. Abstract: Chlorella vulgaris proteins show high potential for food applications. The challenge of biorefinery is to choose the best processes coupling which can ensure the integrity of the molecules and limit energy consumption. This study aimed at understanding the impact of biomass concentration and physicochemical conditions during cell disruption, on the whole process (bead milling (BM), centrifugation, microfiltration). The best scenario tested (BM: 60 g/LDW, 10 °C, lysate dilution: 30 g/LDW, pH 7, 20 °C before centrifugation and filtration of the supernatant at a volume reduction ratio VRR = 3) allowed a soluble protein recovery η S = 12 % with a limited energy consumption of 10 kW h/g protein. Coupling BM at 90 g/LDW, pH 7, a dilution at 20 °C, with NaCl 0.1 M at 30 g/LDW and filtration at VRR = 20 would lead to η S >25 %. The final soluble proteins contained no green pigment; their purity increased from 5 % in the raw biomass to 22 % in the permeate.